1999
DOI: 10.1046/j.1365-2958.1999.01646.x
|View full text |Cite
|
Sign up to set email alerts
|

Histidine kinases: diversity of domain organization

Abstract: Histidine kinases play a major role in signal transduction in prokaryotes for the cellular adaptation to environmental conditions and stresses. Recent progress in the three‐dimensional structure determination of two representative members of histidine kinases, EnvZ (class I) and CheA (class II), has revealed common structural features, as well as a kinase catalytic motif topologically similar to those of the ATP‐binding domains of a few ATPases. They have also disclosed that there are significant differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
192
0
8

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(206 citation statements)
references
References 49 publications
6
192
0
8
Order By: Relevance
“…Comparing the shared elements of TH-CikA, TH-CikA*, TH-CikA∆N and TH-CikA∆G, we hypothesized that either HPK or PsR is required for the interaction that leads to arrhythmia upon overexpression. HPK domains are known to form homodimers through a specific subdomain, which is also the platform for interaction with its cognate RR (Dutta et al, 1999). Furthermore, we confirmed that active CikA is a dimer in solution (Fig.…”
Section: Overexpression Of Psr-containing Cika Variants Causes Arrhytsupporting
confidence: 75%
See 2 more Smart Citations
“…Comparing the shared elements of TH-CikA, TH-CikA*, TH-CikA∆N and TH-CikA∆G, we hypothesized that either HPK or PsR is required for the interaction that leads to arrhythmia upon overexpression. HPK domains are known to form homodimers through a specific subdomain, which is also the platform for interaction with its cognate RR (Dutta et al, 1999). Furthermore, we confirmed that active CikA is a dimer in solution (Fig.…”
Section: Overexpression Of Psr-containing Cika Variants Causes Arrhytsupporting
confidence: 75%
“…Bioinformatics analysis showed the HPK domain of CikA to be related to the class I histidine kinases as exemplified by EnvZ, whose structure has been partially determined (Dutta et al, 1999). Thus, the C-terminal portion of dimeric CikA (Fig.…”
Section: Model For Function Of Cikamentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, the phosphate is passed from the DD to the receiver domain of the RR. The only known exception is the chemotactic two-component system, where the phosphate is passed, not from the DD, but from a histidinecontaining phosphotransfer domain, to the receiver domain of the RR (10). Therefore, in this work, we have eliminated the chemotactic proteins, and we will refer to the receiver domain of a RR protein simply as ''RR.…”
mentioning
confidence: 99%
“…The residues Cys 170 /Phe 175 was found to be crucial in the CqsSvc as it signifies the ligand chain length [44]. The CqsSvc Sensor histidine kinases has a N-terminal transmembrane sensing domains, dimerization histidine phosphotransfer (DHp) domains and C-terminal catalytic ATPbinding (CA) domains [48]. It has been theoretically defined to have two-state model for histidine kinases with a ''kinase on'' and a ''kinase off'' mechanism [49].…”
Section: Cqssmentioning
confidence: 99%